(untitled) (AYUSHDHARA, 2019)
Background: Garbhini Paricharya (Antenatal care) has got its own importance in the traditions, cultures and in medical fraternity from time immemorial. A special diet, unique life style and significant importance have been given to the pregnant women. Supplementation of Madhuraushadha having Rasayana properties, emphasized in the Garbhini Upachara, imparts Deerghayu, Medha, Arogya, Smriti, Prabha, Varna, Deha Bala, Indriya Bala etc. Incorporating such a therapy in Garbhini Paricharya not only benefits the pregnant lady but also for the growing baby in her womb. Objective: To evaluate the efficacy of Madhuraudhadha Siddha Avaleha as Garbhini Rasayana in 6th and 7th month of pregnancy and its influence on maternal immune system. Material and method: It is a randomized comparative clinical trial wherein 30 pregnant ladies fulfilling the selection criteria were randomly divided to 2 groups. The trial group (n=15) was given Madhuraushadha Siddha Avaleha 12gm, twice a day. In the control group (n=15) calcium (Shelcal 500mg) and iron (Heam-up Gems 200mg) supplements were administered once a day during 6th and 7th month of pregnancy. Result: Patients treated with Madhuraushadha Siddha Avaleha showed significant results in maternal weight gain (P<0.001), increase in the maternal immunity level IgG (P=0.030), IgM (P=0.011), increase in serum calcium levels (P=0.005) and also in overcoming the physiological hindrances of pregnancy mainly loss of appetite (P<0.001), heart burn (P<0.001), constipation (P=0.019) etc. Conclusion: The present study confirms the nutritional benefits, Rasayana action and immuno- modulatory effect of Madhuraushadha Siddha Avaleha fulfilling the overall nutritional needs during the 6th and 7th month of pregnancy.